2020
DOI: 10.1002/nafm.10473
|View full text |Cite
|
Sign up to set email alerts
|

Response of Fish Assemblages to Habitat Changes and Fishing Activity in a Tributary of the Jinsha River in Southwest China

Abstract: Reservoir impoundment affects fish habitat condition, in turn likely influencing the spatial and temporal distribution patterns of fish assemblage structure in the impounded area. Fishing activity and instream gravel and sand mining are important anthropogenic factors, and flow discharge, water temperature, and precipitation are important natural environmental variables; both anthropogenic and natural factors likely have impacted fish assemblage structure in impounded and unimpounded waterbodies. We used multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In addition, hydropower cascade development contributes to the main causes of species diversity and community structure changes. Since the implementation of the Jinsha River upstream cascade, the river flow rate dropped significantly, and the decrease in water reduced the river-wetted perimeter area, water flow velocity change, and channel depth; additionally, the dissolved oxygen and habitat changes resulted in reduced fish survival in the reservoir area [ 4 , 5 ]. In this study, we found that the temporal and spatial distributions of Schizothoracinae were positively correlated with flow velocity and dissolved oxygen, and there was more biomass and larger particle-size classes in tributaries with higher flow velocity and dissolved oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, hydropower cascade development contributes to the main causes of species diversity and community structure changes. Since the implementation of the Jinsha River upstream cascade, the river flow rate dropped significantly, and the decrease in water reduced the river-wetted perimeter area, water flow velocity change, and channel depth; additionally, the dissolved oxygen and habitat changes resulted in reduced fish survival in the reservoir area [ 4 , 5 ]. In this study, we found that the temporal and spatial distributions of Schizothoracinae were positively correlated with flow velocity and dissolved oxygen, and there was more biomass and larger particle-size classes in tributaries with higher flow velocity and dissolved oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…However, with rapid economic development and hydropower development, the environmental pollution of water bodies is aggravated, leading to habitat fragmentation, spatiotemporal changes in runoff distribution, increased disturbance of the natural habitat environment of fish, and serious threats to river ecosystems. In addition to overfishing, fish resources and diversity in the upper reaches of the Jinsha River have shown a declining trend [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sand mining can reshape river terrain, alter fish habitats, destroy benthic animal habitats and fish spawning grounds, and is one of the main drivers of freshwater wetland ecosystem degradation and biodiversity decline in the basin [4][5][6][7]. Ecological problems caused by irregular sand mining exist in river basins around the world, such as the Chalakudy, Periyar, and Muvattupuzha river basins in India, the shrinkage of Tonlé Sap Lake in Southeast Asia, and the degradation of fish habitats in California River basin in the United States [8][9][10].…”
Section: Introductionmentioning
confidence: 99%